Perioperative gum-chewing training prevents a decrease in tongue pressure after esophagectomy in thoracic esophageal cancer patients: a nonrandomized trial - Reiko Yamanaka-Kohno; Yasuhiro Shirakawa; Aya Yokoi; Naoaki Maeda; Shunsuke Tanabe; Kazuhiro Noma; Kazuyoshi Shimizu; Toshiharu Mituhashi; Yoshihide Nakamura; Souto Nanba; Yurika Uchida; Takayuki Maruyama; et al. (Scientific Reports)
Abstract Tongue pressure (TP) decreases significantly after esophagectomy in esophageal cancer patients (ECPs). Meanwhile, 2 weeks of gum-chewing training (GCT) significantly increased TP in healthy university students. We examined whether perioperative GCT would decrease the proportion of patients exhibiting a decline in TP at 2 weeks postoperatively, and prevent postoperative complications, in thoracic ECPs (TECPs). This was a single-center interventional study, and nonrandomized study with a historical control group (HCG). TECPs who underwent first-stage radical esophagectomy were recruited. Thirty-two patients of 40 in the gum-chewing group (GCG) were completed perioperative GCT in 3 times daily. Propensity score matching was performed with covariates related to TP including preoperative age, sex, body mass index, and the repetitive saliva swallowing test result, and yielded a matched cohort of 25 case pairs. Eleven GCG patients [44.0%] exhibited significantly lower TP at 2 weeks postoperatively than before esophagectomy was significantly fewer than that of 19 patients [76.0%] in the HCG. The median number of fever days (≥ 38.0 °C) in the 2 weeks after esophagectomy in the GCG was significantly fewer than those in the HCG. Perioperative GCT may prevent postoperative TP decline and postoperative dysphagia-related complications after esophagectomy.